ECONOMIC BURDEN OF THE MOST COMMON INFECTIOUS DISEASES IN CHILDREN IN SLOVENIA - Pokrajac, Tatjana (International Journal of Research -GRANTHAALAYAH, 2022)
Background: In Slovenia, infectious diseases are in children are common cause of visits to primary care physicians, of hospital admissions and the cause of death. They also represent a significant economic burden. Methods: We analyzed routinel calculated data from the data bases of the National Institute of Public Health of the Republic of Slovenia International Journal of Research Granthaalayah (2022), National Institute of Public Health of the Republic of Slovenia (2022) for the time period 2005. We analyzed data with the particular attention on the most frequent or the most expensive infectious diseases of children, Data were classified from recommended literature from CDC Atlanta, according to the most to the International Classification of diagnoses ICD-9 precoded to ICD-10.Results: Our cost estimate is made from a disease costing model, included estimates of direct and indirect costs for selected infectious diseases in 2005. The cost was amounted to EUR 14620187 for children aged 0 to 6 years and EUR 4408773 for children aged 7 to14 years, which account for a 16.97% share of all diseases for children aged 0-6 years and 17.3% of all diseases for children aged 7-14 years. This cost included the cost of first examination in general practice at the primary level, costs, prices calculated from the first examination by a specialist at the secondary level, the cost of hospital of treatment, and the cost of the lost human capital. For children aged 0 to 6 years has the highest costs due to lower respiratory tract infectious due to hospital treatment, and upper respiratory infectious due to visit a doctor. For children aged 7 to 14 years costs were higher of abdominal and intestinal infectious due to hospital treatment and upper respiratory infections due to visit a doctor. Conclusions: In the analysis we estimated the burden of common infectious diseases of children in Slovenia and related economic costs by using routinely collected data. The results are important for monitoring and forecasting health care and health care cost in Slovenia. We expect that the use of information on the burden will bring about more attention to the quality and completeness of the clinical data Preedy and Watson (2010).